Feminist transformations and domestic violence activism in divided Berlin : 1968-2002 - Freeland, Jane (A British Academy monograph, 2022)
This is the first in-depth historical study of feminist activism against domestic violence in divided Berlin between 1968 and 2002. Starting in the 1970s, feminists in West and then East Berlin campaigned against domestic violence as a key issue of women's inequality. They exposed the harmful gender norms that left women unprotected and vulnerable to abuse in the home and called for this to change. Indeed, domestic violence has been one of the issues most effectively addressed by the women's movement in Germany. Since the first shelter opened in West Berlin in 1976, women's shelters have spread throughout the country, and today up to 45,000 women a year turn to emergency housing in Germany, with many more accessing helplines and crisis centres. Situating domestic violence activism within a broader history of feminism in post-war Germany, Feminist Transformations traces the evolution of this movement both across political division and reunification and from grassroots campaign to established, professionalised social service. In doing so, it brings the histories of feminism in East and West Berlin together for the first time and explores how feminism successfully changed women's rights in Germany. But it also asks what popular and political support for domestic violence activism has meant for feminism and the advancement of women's rights more broadly. Examining the trajectory of feminism in Germany, Jane Freeland reveals the limitations of gender equality as advancements in women's rights were often built on the reassertion of patriarchal gender roles.